Analisis Rasio Likuiditas, Solvabilitas Dan Rentabilitas Koperasi Simpan Pinjam (Studi pada Koperasi Simpan Pinjam CU Kolping di Sumba Tengah) - Siti Suryani; Yeni R.L. Niri (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2013)
Cooperative or “koperasi” is an economic organization that has social character as a joint venture of community based on the principle of togetherness and mutual assistance in carrying out its function as economic organizations, cooperatives that drive the people economy and business entities have roles to implement the prosperous society based on Pancasila and the Constitution of 1945. Cooperative also refers to as the pillar of the national economy and is expected to stay strong against the economic shocks in Indonesia. The presence of the cooperative is expected to improve the welfare of its members. Kolping Credit Union (CU Kolping) started with 50 members; it develops rapidly over the years and later becomes a Cooperative Savings and Loans (KSP) CU Kolping. This study aims to determine the ratio of liquidity, solvability and profitability of savings and loans cooperative in Kolping CU of Central Sumba. The data collection techniques use documentation. The results shows that over the past two years the average of liquidity ratio which is seen from the ability to pay its obligations at any time which have a good value, but the ability to rotate assets considered to be less good. Solvability ratio which is visible from its ability to pay its obligations if the cooperative is liquidated has good ratings, both for total assets to total debt ratio and nett worth to debt ratio. The profitability ratio that is visible from the ability of cooperative in securing the whole funds of investment either invested or own capital funds has less value, but good profitability. Key words: Liquidity, Solvability, Rentability